The concept of neutrality: a new approach. Issue 1 (20th September 2019) - Macdonald, Stephen; Birdi, Briony
Abstract : Purpose: Neutrality is a much debated value in library and information science (LIS). The "neutrality debate" is characterised by opinionated discussions in contrasting contexts. The purpose of this paper is to fill a gap in the literature by bringing these conceptions together holistically, with potential to deepen understanding of LIS neutrality. Design/methodology/approach: First, a literature review identified conceptions of neutrality reported in the LIS literature. Second, seven phenomenographic interviews with LIS professionals were conducted across three professional sectors. To maximise variation, each sector comprised at least one interview with a professional of five or fewer years' experience and one with ten or more years' experience. Third, conceptions from the literature and interviews were compared for similarities and disparities. Findings: In four conceptions, each were found in the literature and interviews. In the literature, these were labelled: "favourable", "tacit value", "social institutions" and "value-laden profession", whilst in interviews they were labelled: "core value", "subservient", "ambivalent", and "hidden values". The study's main finding notes the "ambivalent" conception in interviews is not captured by a largely polarised literature, which oversimplifies neutrality's complexity. To accommodate this complexity, it is suggested that future research should look to reconcile perceptions from either side of the "neutral non-neutral divide" through an inclusive normative framework. Originality/value: This study's value lies in its descriptive methodology, which brings LIS neutrality together in a holistic framework. This framework brings a contextual awareness to LIS neutrality lacking in previous research. This awareness has the potential to change the tone of the LIS neutrality debate.